2012
DOI: 10.1021/es302386v
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Aging of Biomass Burning Organic Aerosol by Use of Mixing Ratios: A Meta-analysis of Four Regions

Abstract: Characteristic organic aerosol (OA) emission ratios (ERs) and normalized excess mixing ratios (NEMRs) for biomass burning (BB) events have been calculated from ambient measurements recorded during four field campaigns. Normalized OA mass concentrations measured using Aerodyne Research Inc. quadrupole aerosol mass spectrometers (Q-AMS) reveal a systematic variation in average values between different geographical regions. For each region, a consistent, characteristic ratio is seemingly established when measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
147
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 121 publications
(175 citation statements)
references
References 65 publications
28
147
0
Order By: Relevance
“…Average ratios for individual flights sampling aged emissions range from 0.056 ± 0.003 (B624) to 0.114 ± 0.003 (B622), giving an overall range of 0.058. The level of average OA / CO for fresh emissions from boreal forest fires during BORTAS falls between the upper extent derived from the eucalypt forests of northern Australia during the Aerosol and Chemical Transport in Tropical Convection (ACTIVE) campaign (0.329), and lower ratios from several other campaigns where OA enhancements were comparatively reduced (0.019-0.065; Jolleys et al, 2012). Average OA / CO from aged plumes during BORTAS was again within the range identified from previous field observations, although with closer proximity to ratios from the lower extent of the observed range, including aged boreal forest fire plumes sampled during the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) campaign .…”
Section: Spatial and Temporal Variability In Bb Emissions Propertiesmentioning
confidence: 77%
See 4 more Smart Citations
“…Average ratios for individual flights sampling aged emissions range from 0.056 ± 0.003 (B624) to 0.114 ± 0.003 (B622), giving an overall range of 0.058. The level of average OA / CO for fresh emissions from boreal forest fires during BORTAS falls between the upper extent derived from the eucalypt forests of northern Australia during the Aerosol and Chemical Transport in Tropical Convection (ACTIVE) campaign (0.329), and lower ratios from several other campaigns where OA enhancements were comparatively reduced (0.019-0.065; Jolleys et al, 2012). Average OA / CO from aged plumes during BORTAS was again within the range identified from previous field observations, although with closer proximity to ratios from the lower extent of the observed range, including aged boreal forest fire plumes sampled during the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) campaign .…”
Section: Spatial and Temporal Variability In Bb Emissions Propertiesmentioning
confidence: 77%
“…However, under ambient conditions the importance of SOA addition relative to primary (POA) emissions is more disputable. Despite widespread evidence for the increasing oxygenation of BBOA with aging (Capes et al, 2008;DeCarlo et al, 2008;Cubison et al, 2011;Jolleys et al, 2012), net mass enhancements are not observed consistently. The underlying causes of this variable SOA contribution, including the implications of initial OA composition, also remain ambiguous and require further refinement.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations